1989
DOI: 10.1016/0378-1097(89)90298-x
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification and characterization of hemolysins from Listeria ivanovii and Listeria monocytogenes Sv4b

Abstract: SUMMARYIn culture supematants of both Listeria ivanovii and Listeria monocytogenes Sv4b, for the first time a hemolysin of molecular weight 58 kDa was identified, which had all the characteristics of an SH-activated cytolysin, and which was therefore identified as Iisteriolysin 0 (LLO). In the case of L. ivanovii a second major supematant protein of molecular weight 24 kDa co-purified with LLO. However, the function of this protein has to be determined. In culture supematants of L. ivanovii a sphingomyelinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 7 publications
(7 reference statements)
0
18
0
Order By: Relevance
“…Ivanolysin (ILO) and listeriolysin (LLO) are closely related extracellular proteins produced by L. ivanovii and L. monocytogenes (23,39). These haemolysins belong to the sulfhydryl (SH)-activated group of bacterial toxins expressed by diverse species of grampositive bacteria and are the only thiol-activated toxins produced by intracellular bacteria (22,40).…”
Section: Discussionmentioning
confidence: 99%
“…Ivanolysin (ILO) and listeriolysin (LLO) are closely related extracellular proteins produced by L. ivanovii and L. monocytogenes (23,39). These haemolysins belong to the sulfhydryl (SH)-activated group of bacterial toxins expressed by diverse species of grampositive bacteria and are the only thiol-activated toxins produced by intracellular bacteria (22,40).…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that LLO, the principal virulence factor of L. monocytogenes, plays a pivotal role in the generation of host resistance by induction of Th1 cytokines such as IL-12, IL-18, and IFN-␥ (29,30,36). L. ivanovii is known to secrete ILO, which is highly homologous to LLO (20,40). They have similar signal sequences (25 amino acids in LLO and 24 amino acids in ILO), and the secreted form of both proteins is 504 amino acids long (Fig.…”
Section: Ifn-␥-inducing Ability Of L Monocytogenes and L Ivanoviimentioning
confidence: 99%
“…Both listeriolysin O (LLO), an hly gene product in L. monocytogenes, and ivanolysin O (ILO), an ilo gene product in L. ivanovii, are 58-kDa secretory proteins that are the major virulence determinants in each (12,20,40). They show 80% homology in amino acid sequence (14,16) and belong to a family of cholesterol-dependent cytolysins (CDCs) characterized by the presence of a highly conserved undecapeptide sequence (ECTGLAWEWWR) located near the C terminus (7,42).…”
mentioning
confidence: 99%
“…These toxins include the species-specific types of Iisteriolysin 0 produced by the three Listeria species which are hemolytic on blood agar: Listeria monocytogenes (pathogenic for man anct animals), Listeria ivanoL·ii (animal pathogen) and Listeria seeligeri (apathogenic). Their Iisteriolysins have previously bet!n characterized biochemically [6,10],and it has also been shown that they vary in cytolytic activity.The gene for Iisteriolysin 0 (h/y) from 1.4. monocytogenes has been cloned and sequenced [4,13] and homologous DNA sequences have been detected in the chromosome of the two other hemolytic Listeria species [11]. lt has been firmly established, that Iisteriolysin 0 (LLO) is an essential virulence factor of L. monocytogenes (reviewed in Refs.…”
mentioning
confidence: 99%
“…These toxins include the species-specific types of Iisteriolysin 0 produced by the three Listeria species which are hemolytic on blood agar: Listeria monocytogenes (pathogenic for man anct animals), Listeria ivanoL·ii (animal pathogen) and Listeria seeligeri (apathogenic). Their Iisteriolysins have previously bet!n characterized biochemically [6,10],and it has also been shown that they vary in cytolytic activity.…”
mentioning
confidence: 99%